Effect of Spinal Cord Stimulation on Gait in a Patient with Thalamic Pain. (7th August 2016) - Yozu, Arito; Sumitani, Masahiko; Shin, Masahiro; Ishi, Kazuhiko; Osumi, Michihiro; Katsuhira, Junji; Chiba, Ryosuke; Haga, Nobuhiko
Abstract : Thalamic pain is a central neuropathic pain disorder which occurs after stroke. Its severe chronic pain is often intractable to pharmacotherapies and affects the patients' activities of daily living (ADL) and quality of life (QOL). Recently, spinal cord stimulation (SCS) has been reported to be effective in relieving the pain of thalamic pain; however, the effect of SCS on gait performance in patients is unknown. Therefore, we evaluated the gait performance before and after SCS in a case with thalamic pain. A 73-year-old male with thalamic pain participated in this study. We evaluated the gait of the patient two times: before SCS insertion and after 6 days of SCS. At the second evaluation, we measured the gait in three conditions: stimulation off, comfortable stimulation, and strong stimulation. SCS succeeded in improving the pain from 7 to 2 on an 11-point numerical rating scale. Step frequency and the velocity of gait tended to increase between pre- and poststimulation periods. There were no apparent differences in gait among the three stimulation conditions (off, comfortable, and strong) at the poststimulation period. SCS may be effective on gait in patients with thalamic pain.